2014
DOI: 10.15288/jsad.2014.75.447
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of an Educational Intervention on Alcohol Consumption, At-Risk Drinking, and Health Care Utilization in Older Adults: The Project SHARE Study

Abstract: ABSTRACT. Objective:The purpose of this study was to examine the effectiveness of a patient-provider educational intervention in reducing at-risk drinking among older adults. Method: This was a cluster-randomized controlled trial of 31 primary care providers and their patients ages 60 years and older at a community-based practice with seven clinics. Recruitment occurred from July 2005 to August 2007. Eligibility was determined by telephone and a baseline mailed survey. A total of 1,186 at-risk drinkers were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
3
14

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(109 citation statements)
references
References 22 publications
1
91
3
14
Order By: Relevance
“…Participants were recruited from three health care organizations located in Southern California. Participants aged 55 and older were identified as at-risk drinkers using the Co-morbidity Alcohol Risk Evaluation Tool (CARET) [2324]. The CARET is a measure to identify at-risk drinking older adults.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were recruited from three health care organizations located in Southern California. Participants aged 55 and older were identified as at-risk drinkers using the Co-morbidity Alcohol Risk Evaluation Tool (CARET) [2324]. The CARET is a measure to identify at-risk drinking older adults.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have shown that brief behavioral counseling interventions provided by primary care physicians have reduced alcohol misuse in adults [19, 20] and that these interventions were also effective for the older adult population [21–24]. In addition, alcohol screening and counseling in primary care has been shown to be both cost effective from the health system perspective and cost saving from the societal perspective [25].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike PRISM-E, which compared integrated and enhanced referral care—neither of which were usual care, these RCTs compared various intervention models with usual care (44–47). In all trials, there were significantly higher reductions in alcohol misuse for integrated care compared to usual care.…”
Section: Discussionmentioning
confidence: 99%
“…Disappointingly, only two RCTs (Moore et al, 2010;Ettner et al, 2014) found a statistically significant advantage of intervention over CAU. However, in all but one trial, the outcome variable (number of drinks, number of patients drinking at-risk, and score on AUDIT) decreased significantly in both intervention and CAU groups.…”
Section: Treatment Of Alcohol Use Disorders In the Elderly: An Overvimentioning
confidence: 96%
“…One study (Oslin, 2005), identified by Moy et al (2011), was not included in the review by Kuerbis et al (2013). With an additional literature search for the preparation of this editorial, two RCTs were found that have been published very recently (Ettner et al, 2014;Vrdoljak et al, 2014). Thus, at least 15 RCTs are published on the treatment of AUD (see reference lists of all RCTs).…”
Section: Treatment Of Alcohol Use Disorders In the Elderly: An Overvimentioning
confidence: 99%